2016
DOI: 10.1038/nature20148
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation of Sputnik Planitia implies a subsurface ocean on Pluto

Abstract: The deep nitrogen-covered basin on Pluto, informally named Sputnik Planitia, is located very close to the longitude of Pluto's tidal axis and may be an impact feature, by analogy with other large basins in the Solar System. Reorientation of Sputnik Planitia arising from tidal and rotational torques can explain the basin's present-day location, but requires the feature to be a positive gravity anomaly, despite its negative topography. Here we argue that if Sputnik Planitia did indeed form as a result of an impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 37 publications
5
103
0
1
Order By: Relevance
“…Overall, considering a 50% uncertainty on the initial results, leads to an ice layer thickness between 1.9 km and 8.5 km. Interestingly, this independent estimate agrees very well with our previous results and with previous estimates [ Trowbridge et al , ; Nimmo et al , ].…”
Section: Sputnik Planitia As a Volumetrically Heated Systemsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, considering a 50% uncertainty on the initial results, leads to an ice layer thickness between 1.9 km and 8.5 km. Interestingly, this independent estimate agrees very well with our previous results and with previous estimates [ Trowbridge et al , ; Nimmo et al , ].…”
Section: Sputnik Planitia As a Volumetrically Heated Systemsupporting
confidence: 93%
“…The exact ice layer thickness is, however, unknown. Assuming that Sputnik Planitia is located on a huge impact crater, as suggested by the formation mechanism proposed by Bertrand and Forget [], Nimmo et al [] propose an upper bound of about 7 km based on impact craters on the Moon and Iapetus, while Trowbridge et al [] suggest a minimum thickness of about 5 km in order to keep the observed icebergs afloat. On the basis of these estimates, we can only exclude ice layer thickness above 10 km.…”
Section: Sputnik Planitia Composition and Propertiesmentioning
confidence: 99%
“…It is thought that tidal heating or convective upwellings may generate eutectic melting beneath chaos terrain on Europa (Sotin et al, 2002), and perhaps beneath double ridges on Europa (Nimmo & Gaidos, 2002). If the volatile-rich near-surface of an icy satellite is reheated, such as during a period of tidal heating or by the onset of solid-state convection in the ice shell, eutectic melts could be generated.…”
Section: Discussionmentioning
confidence: 99%
“…Many icy satellites and large Kuiper Belt objects are thought to harbor subsurface oceans of liquid water beneath ice shells that are tens to hundreds of kilometers thick (Hammond et al, 2013;Hussmann et al, 2006;Khurana et al, 1998;Kivelson et al, 2002;Nimmo et al, 2016;Postberg et al, 2009). Many icy satellites and large Kuiper Belt objects are thought to harbor subsurface oceans of liquid water beneath ice shells that are tens to hundreds of kilometers thick (Hammond et al, 2013;Hussmann et al, 2006;Khurana et al, 1998;Kivelson et al, 2002;Nimmo et al, 2016;Postberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation